Unions and employers' associations in Germany: A survey of their membership, density and bargaining coverage - Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2025)
Trade unions and employers' associations play an important role in Germany not only in wage setting, but also in social policy and labour market regulation. While the majority of companies are organised in employers' associations, less than one fifth of employees are still members of a trade union. Union density has declined substantially over the last decades whereas on the employers' side density has fallen to a lesser extent as most employers' associations have introduced the option of bargaining-free membership. At the same time, the collective bargaining coverage of companies and employees has been reduced drastically. Nowadays, less than half of employees in Germany are formally covered by collective agreements. Nevertheless, collective agreements are still directly or indirectly relevant for three out of four employees, and they are an important anchor for wage setting in the entire economy. The erosion of (multiemployer) bargaining coverage has manifold reasons and has been associated with an increased heterogeneity in wage setting over the last decades. The ongoing falls in both bargaining coverage and union density have prompted a controversial discussion of how to stabilise the German system of industrial relations. – – Gewerkschaften und Arbeitgeberverbände spielen in Deutschland nicht nur bei der Lohnfindung eine wichtige Rolle, sondern auch in der Sozialpolitik und Arbeitsmarktregulierung. Während die Mehrheit der Firmen in Arbeitgeberverbänden organisiert sind, sind nur noch weniger als ein Fünftel der Beschäftigten Mitglied in einer Gewerkschaft. Der Organisationsgrad der Gewerkschaften ist in den letzten Jahrzehnten deutlich zurückgegangen, wohingegen derjenige auf Arbeitgeberseite weniger stark fiel, da die meisten Verbände die Option einer Mitgliedschaft ohne Tarifbindung eingeführten. Zugleich hat sich die Tarifbindung der Betriebe und Beschäftigten drastisch verringert. Heutzutage werden weniger als die Hälfte der Beschäftigten formell von Tarifverträgen abgedeckt. Dennoch sind Kollektivverträge direkt oder indirekt für drei von vier Beschäftigten relevant, und sie stellen einen wichtigen Anker der Lohnsetzung in der gesamten Wirtschaft dar. Die Erosion des (Flächen-)Tarifvertrags hat vielfältige Ursachen und geht mit einer zunehmenden Lohndispersion einher. Die anhaltenden Rückgänge der Tarifbindung und des gewerkschaftlichen Organisationsgrads haben eine kontroverse Diskussion ausgelöst, wie sich das deutsche System der Arbeitsbeziehungen stabilisieren lässt.
Keywords: J51; J52; J53; J58; 330; trade union; employers' association; collective bargaining; bargaining coverage; Germany